Creating an Environment for Pre-Service Teachers to Work with Learners with Special Needs - Burth, Jeanne Hager (Journal of the American Academy of Special Education Professionals, 2016)
In this study, pre-service teachers were afforded the opportunity to participate in two on-campus activities for students with low-incidence disabilities. The project explores the attitudes and perceptions of a group of pre-service teachers before and after participating in two educational experiences with students with low-incidence special needs. An informal educational environment was created on campus to give the pre-service teachers a familiar and casual experience when interacting with learners with cognitive deficits, autism spectrum disorder, physical exceptionalities, and emotional and behavioral disabilities. This study seeks to answer the following questions: (1) Can pre-service teachers’ attitudes towards teaching students with disabilities change by providing them with non-academic experiences with persons who have disabilities? (2) Does a familiar setting impact the pre-service teacher’s knowledge of teaching persons with exceptionalities when participating in a field experience with persons with low-incidence disabilities?